Organizacja przedsiębiorcza, pozytywna i wysoko efektywna dzięki zarządzaniu uwagą organizacyjną - Zbierowski, Przemysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper attempts to put organizational entrepreneurship in the context of high performance and positive organizational scholarship. It also empirically answers the question about driving force of entrepreneurship: is it external, environmental force, or internal force coming from organization members mindsets? The study therefore examines relationships among institutional factors of environment (environment conditions: munificence, dynamism and complexity and dimensions of country institutional profile for entrepreneurship), entrepreneurial attention, and entrepreneurial orientation. Entrepreneurial attention is here defined as noticing, encoding, interpreting and focusing time, energy and effort by organization members on reconciling opportunities and actions in general, and entrepreneurial objects and ideas in particular. The paper presents the conceptualization of entrepreneurial attention and results of empirical research. They prove that the impact of entrepreneurial attention on organizational entrepreneurship is much higher than influence of environmental forces. The paper also opens space for future research in "cross-field" or organizational entrepreneurship, high--performance organizations and positive organizational scholarship. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 714-729